64 511
Assignments Done
99,3%
Successfully Done
In September 2018

Answer to Question #20468 in Algebra for eduardo

Question #20468
3(2x-7)+4-5x=2x(x-4)-(2x^2+3)
Expert's answer
3(2x-7)+4-5x=2x(x-4)-(2x^2+3)
6x-21+4-5x=2x^2-8x-2x^2-3
x-17=2x^2-2x^2-8x-3
x-17=-8x-3
x+8x=-3+17
9x=14
x=14/9

Need a fast expert's response?

Submit order

and get a quick answer at the best price

for any assignment or question with DETAILED EXPLANATIONS!

Comments

No comments. Be first!

Leave a comment

Ask Your question

Submit
Privacy policy Terms and Conditions